Expression and Localization of Stanniocalcin-1 in Bovine Osteoblasts - Dong-yang Liu§, Shi-jin Yang§, Zhao-fang Xi, Liming-Wu, Sen Chen, Shi-qi Dong, Jian-lin Wang and Ding-zong Guo* (Pakistan Veterinary Journal, 2012)
As a novel glycoprotein hormone, Stanniocalcin-1 (STC-1) was first identified in teleost species, and it is involved in the regulation of mineral homeostasis in bony fish and mammals. STC-1 can not only affect the mammals bone development, but also protect neurons from the damage of ischemia, and stimulate the angiogenic response. Although it is widely expressed in rodent skeletons, whether this hormone is expressed in the skeleton of ruminant animals, like bovines, is still unknown. Here, we investigated the expression of STC-1 in bovine osteoblasts by using immunocytochemical staining and RT-PCR. Our results show that the mRNA and protein of STC-1 are expressed in the bovine osteoblasts during later differentiation periods 10th day in vitro. The present data support the notion that STC-1 may play a role in the process of bovine bone development.